Respuesta :
Answer: [tex](\frac{1}{8})[/tex])(3 - 4cos 2x + cos 4x)
Step-by-step explanation:
sin⁴ x
= sin²x * sin²x
= [tex]\frac{1 - cos 2x}{2} * \frac{1 - cos 2x}{2}[/tex]
= [tex]\frac{1 - 2cos 2x + cos^{2}2x} {4}[/tex]
= [tex](\frac{1}{4})[/tex](1 - 2cos 2x + cos²2x)
= [tex](\frac{1}{4})[/tex](1 - 2cos 2x + [tex]\frac{1 + cos 4x}{2}[/tex])
= [tex](\frac{1}{4})[/tex](1 - 2cos 2x + [tex]\frac{1}{2}[/tex] + [tex]\frac{cos 4x}{2}[/tex])
= [tex](\frac{1}{4})[/tex]([tex]\frac{3}{2}[/tex] - [tex]\frac{4cos 2x}{2}[/tex] + [tex]\frac{cos 4x}{2}[/tex])
= [tex](\frac{1}{8})[/tex](3 - 4cos 2x + cos 4x)
Answer:
(3 - 4cos(2x) + cos(4x))/8
Step-by-step explanation:
You know that ...
... cos(2x) = cos(x)^2 - sin(x)^2 = 1 - 2sin(x)^2
Then
... sin(x)^2 = (1 -cos(2x))/2
Squaring this, we get ...
... sin(x)^4 = (1/4)(1 - 2cos(2x) +cos(2x)^2)
... = (1/4)(1 - 2cos(2x) +(1 -sin(2x)^2))
Using the above relation for sin^2, we have ...
... sin(x)^4 = (1/4)(2 - 2cos(2x) - (1-cos(4x))/2)
... = (1/8)(3 - 4cos(2x) + cos(4x))